Diseases of stiff-tailed ducks in captivity - Hillgarth, Nigella; Kear, Janet (Wildfowl, 1982)
Results of post-mortem data from 439 stifftails and 24 White-backed Duck dying in Wildfowl Trust collections between 1959 and 1980 have been analysed. The main causes of death are enteritis, pneumonia, tuberculosis and trauma. There was a low level of renal failure, parasite infestation and of aspergillosis.